Effect of probiotic supplementation combined with bismuth-containing quadruple therapy on gut microbiota during Helicobacter pylori eradication: a randomized, double-blind, placebo-controlled trial - Han, Zhongxue; Li, Yueyue; Nan, Xueping; Zhou, Tao; Li, Lixiang; Li, Yanqing (Frontiers in Nutrition, 2024)
Background: Helicobacter pylori (H. pylori) eradication has been reported to affect gut microbiota distribution. This study aimed to evaluate the effect of probiotic supplementation on the gastrointestinal microbiota during eradication and the efficacy of bismuth-containing quadruple therapy.Methods: One hundred treatment-naïve H. pylori-positive patients were randomly assigned 1:1 to receive 14-day bismuth-containing quadruple therapy (esomeprazole, bismuth, amoxicillin, and clarithromycin) combined with the probiotic (Bifidobacterium animalism subsp. lactis BLa80) or placebo. The Gastrointestinal Symptom Rating Scale (GSRS) was completed before and after treatment. Stool samples were collected for 16S rRNA gene sequencing at weeks 0, 2, and 10.No significant difference in the eradication rate was observed between the two groups. The incidence of adverse events, especially nausea (P = 0.029), was lower in the probiotic group. After treatment, the GSRS score decreased significantly in the probiotic group (P = 0.039). The gut microbiota underwent considerable changes immediately following eradication treatment, predominantly characterized by an increase in Proteobacteria at the expense of commensal Firmicutes and Bacteroidota, but gradually returned to baseline after eight weeks. By week 10, beneficial genera such as Lachnoclostridium, Parasutterella, Hungatella, and Akkermansia were notably enriched in the probiotic group. Additionally, the correlation networks in the probiotic group were closer to their initial levels at week 10 compared to the placebo group.Conclusions: Disturbances in the gut microbiota following H. pylori treatment appeared to be temporary, and probiotic supplementation could mitigate antibioticinduced alterations in the gut microbiota. This study also provided evidence supporting the effectiveness of probiotics in alleviating gastrointestinal symptoms.